HEGEMONI DOLAR DAN POTENSI KEMUNCULAN MATA UANG BRICS - Faisal Nurdin Idris; Achmad Maulana Dzaky; Rijalul Haq Fadhlurrahman; Silva Hafsari (Penerbit Media Wawasan Ilmu, 2022)
This research focuses on the question of how there is the potential for the emergence of the BRICS currency. In this case, the emergence of the BRICS currency will lead to a renewal of the system in global monetary policy. The research methodology uses qualitative because this research is descriptive and uses analysis. The use of qualitative design aims to build understanding through explanations sourced from several literatures such as journals, books and articles. In order to answer the research questions, exchange rates and foreign policy are taken as analytical tools. After conducting research, it was found that the potential for the emergence of the BRICS currency was caused by long-standing dependence on US dollar hegemony, this was considered to only benefit the US, not developing countries. The BRICS currency is considered to have less potential because it requires a large financial infrastructure and has to be able to compete with the World Bank, so that the renminbi is deemed appropriate to become the BRICS currency. Several currency principles also play a role in determining whether or not a global currency is ideal, such as the factors of “safety, liquidity and returns”. In this case, the renminbi has not been able to balance these three factors so that if the meaning of the BRICS Currency is renminbi, then the renminbi cannot be used as a global reserve currency as a competitor to the US dollar, therefore the renminbi is ideal to be designated as Regional Currency in Asia